Open Source Web Application (HealthTest) for Emotional Health and Wellness Management in University Students: Development and Usability Study - Lucrecia Llerena; Daisy Nata Castro; Nancy Rodriguez; Donald Silva Sánchez (Online Journal of Public Health Informatics)
Abstract BackgroundEmotional health plays a fundamental role in quality of life, particularly after the COVID-19 pandemic, which has increased stress and anxiety, especially among children and young people. ObjectiveThis study aimed to focus on the early identification of emotional processes that affect individuals’ well-being and their effective management. MethodsThe open-source web app HealthTest was developed to help users understand and manage their emotions through tests focused on aspects such as stress, anxiety, and depression. The Open Source Scrum (OSCRUM) framework was used to optimize collaboration and effectively achieve objectives. ResultsHealthTest has established itself as a valuable tool for mental health professionals by gathering data from seventh-semester software engineering students and external users. It identifies trends in stress, anxiety, and depression through user self-assessments. In addition, it provides meditation and relaxation resources designed to support users in managing their emotional well-being. ConclusionsThis study promotes accessibility to self-care and health care tools. HealthTest reaffirms its commitment to benefiting both mental health professionals and patients, providing an effective avenue for controlling and improving emotional well-being.